Training needs for Arabic teachers in the second cycle schools In Tartous, from the point of view of the specialized teachers (Journal of Hama University, 2020)
The research aims to identify the training needs of the Arabic language teachers in the second cycle of basic education schools in Tartous Governorate, and the differences between the average degrees of the answers of the individuals in the research sample to the questionnaire of training needs for Arabic language teachers in the second cycle of basic education schools in Tartous Governorate according to variables: (gender, Educational qualification, number of years of experience, number of training courses). The current research relied on the descriptive analytical approach, and the research tool consisted of a questionnaire prepared by the researcher and studied psychometrically, and the research sample consisted of (444) teachers, with a representation rate of (45.49%) of the original community, and the research reached the following results: 1- There were no statistically significant differences between the mean scores for the answers of the members of the research sample to identify the training needs of Arabic language teachers according to the gender variable.2- There are statistically significant differences between the average scores for the answers of the members of the research sample on the questionnaire of training needs for Arabic language teachers according to the variable of the educational qualification in favor of teachers who do not have an educational qualification.3- There are statistically significant differences between the average scores for the answers of the members of the research sample on the questionnaire of training needs for Arabic language teachers according to the variable number of years of experience in favor of teachers who have years of experience (5 years or less).5- There are statistically significant differences between the average scores for the answers of the members of the research sample on the questionnaire of training needs for Arabic language teachers according to the variable number of training courses in favor of (two courses or less).